Factory-Outlet-Center: Discount oder Disney? Eine explorative Analyse der Auswirkungen von Erlebnismarketing auf die Attraktivität von Factory-Outlet-Centern - Celine C. Gildemeister; Audrey Mehn; Jens K. Perret (Books on Demand (BoD), 2021)
– The presented study analyzes the effects of experience marketing on the attractiveness of German factory-outlet-centers (FOC). Due to a changing competitive landscape and societal value changes, the retail sector has to find new ways to remain attractive for consumers, one of this is the use of experience marketing. In FOC, however, this development has not been realized in its entirety. The empirical study answers the question whether FOCs have overseen the relevance of changing market conditions or if there is no demand for experiences and entertainment in FOCs. Another focus of this study is to evaluate how far these marketing approaches have the potential to increase the FOCs attractiveness. The results indicate that experience marketing is less predominant for center visitors and customers than low prices and discounts. Furthermore, it shows that only omni-channel initiatives bear the potential to attract customers to a FOC.
urn:nbn:de:101:1-2021021900063971390174
Keywords: 650; Direktvertrieb; Einkaufszentrum; Event-Marketing; Deutschland